Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada PT Herona Express Pamulang - Suworo, Suworo; Sagita, Putri Dinda (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The rapid growth of the logistics service industry in Indonesia has intensified competition among shipping companies, emphasizing the importance of service quality and pricing strategies in enhancing customer satisfaction. This study aims to examine the effect of service quality and price on customer satisfaction at PT Herona Express, a logistics company operating in Pamulang, Indonesia, that utilizes rail-based and truck-based transportation services. Using a quantitative research approach, the study surveyed 100 respondents selected through the Slovin formula with a 10% margin of error. Data were collected using questionnaires and analyzed through validity and reliability testing, classical assumption tests, linear regression (both simple and multiple), as well as correlation and determination coefficients. The findings indicate that service quality has a significant positive effect on customer satisfaction, with a correlation coefficient of 0.857 and a determination coefficient of 73.4%. Similarly, price also shows a significant positive influence with a correlation coefficient of 0.798 and a determination coefficient of 63.7%. When analyzed simultaneously, service quality and price jointly contribute to customer satisfaction with a combined R² value of 76.1% and an F-test result of 154.627 (Sig. < 0.001). These results highlight the strategic importance of enhancing both service quality and competitive pricing to improve customer satisfaction in the logistics sector.